Electronic resource management in libraries [electronic resource] : research and practice - Breivold, Scott; Yu, Holly (Information Science Reference, 2008)
"This book provides comprehensive coverage of the issues, methods, theories, and challenges connected with the provision of electronic resources in libraries, with emphasis on strategic planning, operational guidelines, and practices. Its primary focus